Ancaman dan Langkah Pengamanan Sistem Informasi Menggunakan Metode Systematic Literature Review - Achmad Mukhlis; Baiq Laila Alfila; Aliya Zhafira Wastuyana (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to analyze security threats that occur in information systems and ways to overcome them. The method used in this research is Systematic Literature Review, where articles related to security threats in information systems are collected and analyzed qualitatively. The results show that there are various kinds of security threats in information systems, such as hacking, sabotage, espionage, and others. These threats can damage data, steal information, or disrupt system integrity. To overcome these threats, prevention and treatment efforts are needed. Prevention is done to prevent damage, loss, or theft of data, while treatment is done if data has already been attacked. Some ways to improve information system security include improving HR knowledge related to cyber threats, implementing readiness certification, and adopting security domains from other countries. Mapping the types of cyberattacks and selecting appropriate security technologies are also important. Some other efforts include regular operating system updates, applying encryption to data, controlling access, using firewall technology, and implementing standard operating procedures (SOPs) and privacy policies. This research can serve as a guide in developing effective policies and measures in maintaining information system security.